Severe obstruction of the urinary tract due to talcum powder granuloma after surgery - A case report - (:unkn) unknown (Kluwer Academic Publishers, 1992)
Talcum powder which is generally used for lubrication of surgical gloves can be responsible for granuloma formation with subsequent complications. This is the report of a case with progressive urinary tract obstruction. © 1992 Akadémiai Kiadó.